Intraday Price Discovery in Fragmented Markets - Sait Ozturk; Michel van der Wel; Dick van Dijk (Tinbergen Institute, 2014)
For many assets, trading is fragmented across multiple exchanges. Price discovery measures summarize the informativeness of trading on each venue for discovering the assets true underlying value. We explore intraday variation in price discovery using a structural model with time-varying parameters that can be estimated with state space techniques. An application to the Expedia stock demonstrates intraday variation, to the extent that the overall dominant trading venue (NASDAQ) does not lead the entire day. Spreads, the number of trades and volatility can explain almost half of the intraday variation in information shares.
Keywords: C32; G14; 330; High-frequency data; Market microstructure; Price Discovery; Kalman filter